Exploring the levels of homocysteine and its relationship with cognitive function in children with attention deficit hyperactivity disorder - Wang, Huiting; Liu, Ziqi; Wang, Xin; Zhang, Jianzhao; Yang, Jian (Frontiers in Neurology, 2025)
BackgroundAttention deficit hyperactivity disorder (ADHD) is a neurodevelopmental disorder frequently accompanied by cognitive dysfunction. However, the precise etiology of the cognitive impairment remains unclear. Homocysteine is recognized as a risk factor that contributes to cognitive impairment.ObjectiveTo explore the potential changes in serum homocysteine levels in children with ADHD and to evaluate its relationship with cognitive function.MethodsIn this cross-sectional and case–control study, 39 children diagnosed with ADHD were recruited from the outpatient clinic of the Capital Center For Children’s Health, Capital Medical University, along with 40 age- and sex-matched healthy children from the Health Care Department. Serum homocysteine levels were measured via the enzyme cycle method. Age and sex were incorporated into stratified analyses. Cognitive function in patients with ADHD was evaluated using the Behavior Rating Inventory of Executive Function (BRIEF).ResultsCompared with the healthy individuals, patients with ADHD exhibited significantly higher serum total homocysteine levels (7.20 ± 1.19 μmol/L vs. 6.35 ± 1.11 μmol/L, p = 0.002). This association was prominent in younger patients (7.21 ± 1.39 μmol/L vs. 5.84 ± 0.18 μmol/L, p = 0.001) and male patients (7.21 ± 1.15 μmol/L vs. 6.44 ± 1.18 μmol/L, p = 0.010). No significant correlation was observed between serum total homocysteine levels and BRIEF scores (p > 0.05).ConclusionThe study indicates that compared to healthy individuals, patients with ADHD exhibit relatively high homocysteine levels, especially in younger and male patients. However, this study did not support a significant correlation between homocysteine levels and cognitive function in children with ADHD.